The pattern of facial preferences in boys at early adolescence - Kościński, Krzysztof (Anthropological Review, 2010)
Despite numerous studies on perception of facial attractiveness in adults, preferences in adolescents remain poorly characterized. The aim of present study was to explore facial preferences in boys at early adolescence (11-13 years old) and compare them with preferences of men. All males evaluated the same 30 female faces, which were also assessed by independent judges for several perceived features. Regardless of age, boys assessed attractiveness much the same as men, and the strengths of their preferences for specific facial features were similar to those of men. The pubertal maturity (calculated on the basis of the presence of pubic hair at two sessions spaced ten months apart) correlated positively with strength of preference for several facial features (specifically: maturity, sexiness, marital appearance and friendly appearance). This remained true even after controlling for age and psychosexual development, suggesting that sex hormones are involved in the development of facial preferences in pubescent boys.